Effect of Silk Worms (Tubifex sp.) Feed On Production Performance, Nutri-tion, And Gills Histology of Striped Catfish Fingerlings (Pangasionodon hy-popthalmus): English - Yohanes Corne; Sinung Rahardjo; Moch. Nurhudah; Putu Angga Wiradana; Sudaryatma, Putu Eka (Journal of Aquaculture and Fish Health, 2025)
Natural feed has emerged as an alternative to support production performance and the nutrients contained in fish meat. This study aimed to determine the effect of feeding silk worms (Tubifex sp.) in improving production performance, nutritional content, and gill histology of striped catfish fingerlings (Pangasionodon hypopthalmus). Silkworms were sourced from different origins, namely Group P1 (silkworms with dry food media), Group P2 (commercial silkworms), and Group P3 (wild silkworms). Silkworms were reared for 55 days and fed to catfish seed for 25 days ad libitum.  Feeding had no significant effect on absolute length growth, total biomass, and feed conversion with worm feeding treatment (P1) with values respectively 2.3 ± 0.10%, 6.0 ± 0.38%, and 4.2 ± 0.47%. Likewise, the results of growth rate, weight, and length, group P1 had better results compared to treatments (P2) and (P3) but were not significantly different. The best protein efficiency ratio resulted from treatment (P1) of 0.42 ± 0.25%. Gill histology changes were shown in groups P2 and P3, namely hemorrhage and congestion. Based on these results, silkworms reared in dry media can be an effective natural food for striped catfish fingerlings.